2012
DOI: 10.1086/666615
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Executive Compensation and Job Mobility

Abstract: Fewer women than men become executive managers. They earn less over their careers, hold more junior positions, and exit the occupation at a faster rate. We compiled a large panel data set on executives and formed a career hierarchy to analyze mobility and compensation rates. We …nd that, controlling for executive rank and background, women earn higher compensation than men, experience more income uncertainty, and are promoted more quickly. Amongst survivors, being female increases the chance of becoming CEO. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
158
5
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(193 citation statements)
references
References 28 publications
(30 reference statements)
22
158
5
4
Order By: Relevance
“…These results are consistent with previous studies indicating that women score higher than men in measures of perception of career barriers (Cardoso & Ferreira Marques, 2001;Cardoso & Moreira, 2009;McWhirter, 1997), with subsequent impact in career planning (Cardoso & Moreira, 2009). Indeed, several studies have confirmed differences in various career outcomes across different fields, such as earning, promotions and occupation of executives' positions (Bertrand, Goldin, & Katz, 2010;Gayle, Golan, & Miller, 2012;Ginther & Hayes, 1999;Ginther & Kahn, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous studies indicating that women score higher than men in measures of perception of career barriers (Cardoso & Ferreira Marques, 2001;Cardoso & Moreira, 2009;McWhirter, 1997), with subsequent impact in career planning (Cardoso & Moreira, 2009). Indeed, several studies have confirmed differences in various career outcomes across different fields, such as earning, promotions and occupation of executives' positions (Bertrand, Goldin, & Katz, 2010;Gayle, Golan, & Miller, 2012;Ginther & Hayes, 1999;Ginther & Kahn, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…We find evidence suggesting women are likely to advance professionally in sectors in which their presence is stronger. We find evidence that suggests women are likely to climb professional ladders in sectors where their presence is stronger, a fact that is consistent with the evidence analyzed in Golan, Gayle, and Miller (2012). In our analysis, this empowerment through employment narrative is motivated by the positive and significant correlation (the point estimate is 0.21 with a corresponding p-value of 0.0000) between the average share of female employment and the average share of female-owned firms by sector and country that results after controlling for other observable characteristics of the firm (see Table 7).…”
Section: Hiring Practices Related To the Gender Of Workers And Managesupporting
confidence: 89%
“…See for example, Bertrand and Hallock (2001), Wolfers (2006), Gayle et al (2012), Dezsö and Ross (2012).…”
Section: Female Leadershipmentioning
confidence: 99%
“…See for example, Bertrand and Hallock (2001), Wolfers (2006), Gayle et al (2012), Dezsö and Ross (2012). The literature on other countries is quite thin: see Cardoso and Winter-Ebmer (2010) (Portugal), Ahern and Dittmar (2012) and Matsa and Miller (2013) (Norway), Smith et al (2006) (Denmark), Gagliarducci and Paserman (2015) (Germany), and Flabbi et al (2016a) (Latin America).…”
Section: Introductionmentioning
confidence: 99%